PENGARUH PERCEIVED EASE OF USE DAN TRUST TERHADAP KEPUASAN PENGGUNA DALAM MENGADOPSI PEMBAYARAN E-WALLET SHOPEEPAY PADA MAHASISWA/I UNIVERSITAS NEGERI JAKARTA - Dorojatun Zaidan Latasa Muhammad; Muhammad Fachri Siregar, Muhammad Rafael Faruqi, Naura Artanti Shafwan Wibowo, Ranisya Refanka Adhar (Jurnal Ekonomi dan Bisnis, 2025)
This research examines the influence of perceived ease of use and trust on user satisfaction on ShopeePay E-Wallet users at Jakarta State University. This study uses quantitative methods, with data taken through an online questionnaire distributed via Google Form to 102 respondents selected by purposive sampling. Data analysis was carried out using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach through SmartPLS 4 software. The research findings reveal that perceived ease of use has a positive and significant effect on user satisfaction and trust also states that there is a positive and significant effect on user satisfaction.